ASSESSMENT OF CARBON STORAGE AND SEQUESTRATION BY USING I- TREE PROGRAM FOR ATRUSH FOREST/NORTH OF IRAQ - & Akrawee, Qaro (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to assess the data collected from the Iraqi North forests of Atrush, for reporting the urban forests and their status in many locations with different scales and ranges. This process was carried out by using up-to-date technology. Such technology included the economic scopes of the evaluation ecosystem, by i-Tree Eco evaluation, and the US Forest Service which helps out in such a program. The evaluation included the total carbon storage of 41 species of trees, and it was found that 27.78 t of those trees in which the value of 4743608.35 had an amount of gross carbon sequestration rate of 0.63 t /year and a value of 107.576.431.These results indicated that carbon storage within those trees of different species investigated by the program was not the same and the Oriental plane trees are different and distinguish from other trees in term of their storage of carbon amount and only seven trees had the storage of 20.51 t of carbon with carbon sequestration of 0.32 t. Other species in the sample had less amount of carbon sequestration.